Объяснение:
2(√7+√6)²-5(√7+√6)(√7-√6)+2(√7-√6)²=
=2(7+2√42+6)-5((√7)²-(√6)²+2(7-2√42+6)=
=14+4√42+12-35+30+14-4√42+12=
=14+12-35+30+14+12=47
47
2(+-5+2(-=0 (5ab превратилось в 5 потому что a*b=1)
2(7++6)-5+2(7-+6)=0
2(13+)-5+2(13-)=0
26+-5+2-=0 (сокращаем )
52-5=47
Объяснение:
2(√7+√6)²-5(√7+√6)(√7-√6)+2(√7-√6)²=
=2(7+2√42+6)-5((√7)²-(√6)²+2(7-2√42+6)=
=14+4√42+12-35+30+14-4√42+12=
=14+12-35+30+14+12=47
47
Объяснение:
2(
+![\sqrt[]{6}](/tpl/images/1346/7999/c05c3.png)
-5+2(
-![\sqrt[]{6}](/tpl/images/1346/7999/c05c3.png)
=0 (5ab превратилось в 5 потому что a*b=1)
2(7+
+6)-5+2(7-
+6)=0
2(13+
)-5+2(13-
)=0
26+
-5+2-
=0 (сокращаем
)
52-5=47